The Role of Multichannel Marketing in Customer Retention and Loyalty: Study in Emerald Bank Customer in Indonesia - Ambarwati Ambarwati; Djumilah Zain Hadiwidjojo; Achmad Sudiro; Fatchur Rohman (Department of Management, Faculty of Economics and Business, Brawijaya University, 2014)
Attention on the relationship between customer retention, customer loyalty, and customer satisfaction that serves as